Diversidade e bioprospecção de fungos endofíticos associados aos cactos Melocactus ernestii e Opuntia humifusa presentes em ecossistemas do Brasil e dos Estados Unidos - Alice Ferreira da Silva (2014)
To understand the potentialofthe mycota endophytic associated toCactaceaeplants, this study aimedtocharacterize the diversityofthe endophytic communityofroot, stem and spine fromMelocactus ernestiiVaupel and stems fromOpuntia humifusa(Raf.) Raf. by molecular biology and morphological techniques; and evaluate the potentialofthe crude extracts and metabolitesofM.ernestii,O.humifusaand endophytic fungi on the antimicrobial potential. The taxaAureobasidium pullulanseMycoleptodiscus indicusassociated with stems ofM.ernestiieAlternariacf.arborescens, Alternariasp. 4Aureobasidium pullulansandDiaporthesp. associated with stemsofO.humifusawere dominant; and onlyDiaporthesp. UFMGCB 6350 (potential new species) was shared betweenM.ernestiiandO.humifusa.Preussiasp. 1 andSphaerobolaceaesp. were the dominant species on the spines whileCochliobolus eragrostidis,Fusarium oxysporumandF. solaniwere the dominant species in the roots ofM. ernestii. Among the identified isolates, genera and 24 speciesofM.ernestiiand four genera and four speciesofO.humifusawere first reported as endophytic fungi associated with cacti. A totalof79 endophyte taxa recovered (10 from theO. humifusaand 69 from theM. ernestii) showed low similarity with sequencesoffungi depositedinthe GenBank database and could represent new fungal species. The value on the Margalef index fortheendophyticfungalofO.humifusa(stems=3.4)eM.ernestii(stems=5.7,spines= 5.17 androots= 12.1) showed moderate and high diversity, respectively. The Beta diversity was lower among cladodes and spines (0.65) compared with the other pairs:root and stems (0.85) and root and spines (0.84), suggesting that endophytic communityofroot was themostdifferentiated.Noantifungal activity was observedinthe crude extracts from plants while five extracts of fungal endophytes fromM.ernestiiand six extracts of fungal endophytes fromO.humifusashowed antimicrobial activity for atleastone microorganism tested. The majority presenceofthe fatty acid palmitic was detected to the extractsAlternariasp. 1Ohu8B2,Alternariacf.arborescensOhu 30A,Bartaliniasp.UFMGCB6347,CladosporiumfuniculosumOhu17C1,Fusarium solaniiUFMGCB 5865 andParaconiothyriumsp. Ohu 17A and the fractions 8 and 9 ofAlternariacf.arborescensOhu 13A1. The linoleic acid was majorityinthe fractions 7 and 9 ofBiscogniauxia mediterraneaOhu 19B andinthe fraction 7 ofAlternariacf.arborescensOhu 13A1. Using a bioassay-guided purification approach cytochalasin Hwere obtained fromDiaporthesp. UFMGCB 6350, spiciferone Awere obtained fromPhomasp. UFMGCB 6409 and (-)-5-methylmelleinwere obtained fromBiscogniauxia mediterraneaOhu 19B, that showed weak or moderate antifungal activity against the target microorganisms tested, with the genusPhomopsiswas themostsensitive; the results indicate that these substances can’tbethe unique responsible for the bio-activity initially observedinthe crude extract. To extractBiscogniauxia mediterraneaOhu 19B suggest synergistic effect of (-)-5-methylmellein and linoleic acid. To our knowledge, thisisthefirstreport of bioactive substances produced by endophytic fungi associated with cacti.